2017
DOI: 10.1590/0004-282x20170085
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of brain white matter in Huntington gene mutation individuals

Abstract: Objective: To evaluate the role of the involvement of white matter tracts in huntingtin gene mutation patients as a potential biomarker of the progression of the disease. Methods: We evaluated 34 participants (11 symptomatic huntingtin gene mutation, 12 presymptomatic huntingtin gene mutation, and 11 controls). We performed brain magnetic resonance imaging to assess white matter integrity using diffusion tensor imaging, with measurement of fractional anisotropy. Results: We observed a significant decrease of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…White matter (WM) fiber tracts can be imaged using diffusion tensor imaging (DTI), with the most commonly reported metric being fractional anisotropy (FA) in water diffusion. Reduced FA is observed in HD in many WM regions including the corpus callosum, superior and inferior longitudinal fasciculi, corona radiata, internal capsule and cingulum, indicating microstructural changes to the axon including reduced axonal integrity and demyelination [11][12][13][14] . To query white matter changes in our model, DTI data were collected pre-surgery and 3-, 6-, 9-, 14-, and 20-months post-surgery.…”
Section: Mhtt Delivery Results In Microstructural Changes In Several ...mentioning
confidence: 99%
See 1 more Smart Citation
“…White matter (WM) fiber tracts can be imaged using diffusion tensor imaging (DTI), with the most commonly reported metric being fractional anisotropy (FA) in water diffusion. Reduced FA is observed in HD in many WM regions including the corpus callosum, superior and inferior longitudinal fasciculi, corona radiata, internal capsule and cingulum, indicating microstructural changes to the axon including reduced axonal integrity and demyelination [11][12][13][14] . To query white matter changes in our model, DTI data were collected pre-surgery and 3-, 6-, 9-, 14-, and 20-months post-surgery.…”
Section: Mhtt Delivery Results In Microstructural Changes In Several ...mentioning
confidence: 99%
“…The most highly affected regions are the caudate nucleus and putamen (together comprising the striatum); however numerous brain regions that send afferent connections to the striatum are also affected, including widespread cortical and subcortical brain areas [6][7][8][9][10] . The network of white matter fiber tracts interconnecting the striatum with the cortex also show extensive evidence of degeneration [11][12][13][14] , highlighting that HD is not only a striatal disorder, but rather a disease characterized by a progressive disintegration of cortico-basal ganglia circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion MRI enables the investigation of WM microstructural alterations and provides useful insights into the pathological processes underlying brain atrophy. Diffusion tensor imaging (DTI) has been widely used to explore WM microstructural changes in HD and alterations have been observed in several brain regions including the corpus callosum, corona radiata, internal and external capsules, thalamic radiations, corticospinal tract, the cingulate gyrus and longitudinal fasciculus 5,[8][9][10][11] . Most studies have reported reduced fractional anisotropy (FA) and elevated mean diffusivity (MD) in the WM of patients with HD compared to controls, suggesting axonal degeneration.…”
Section: Multiparametric Characterization Of White Matter Alterations...mentioning
confidence: 99%
“…The scale was used in six neuroimaging studies, 75 , 83 , 85 , 87 , 94 , 95 eight cognitive studies, 74 , 82 , 84 , 88 , 89 , 91 , 93 , 96 and three studies examining other clinical aspects of HD (eg, balance, dysphagia) 80 , 90 , 92 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, all the diagnostic test accuracy studies 71 , 72 , 76–78 were published before 2017. In the last 4 years, 14 studies reported the use of MoCA in HD patients: one prevalence study, 86 five neuroimaging studies, 83 , 85 , 87 , 94 , 95 six cognitive studies, 84 , 88 , 89 , 91 , 93 , 96 and two studies investigating clinical aspects of HD 90 , 92 . Nonetheless, the last diagnostic test accuracy study was done in 2013 77 …”
Section: Discussionmentioning
confidence: 99%